Whistleblowing and the 'Person-Situation' Conundrum: What Matters More?. (September 2021) - Gakhar, Meenal; Mulla, Zubin R.
This article extends the knowledge on whistleblowing by studying the impact of two individual antecedents (moral foundations and personality traits) and two situational factors (ethical leadership and leader–member exchange) on whistleblowing intentions. We presented 203 management students with a situation and assessed their likelihood of whistleblowing. Model estimations found strong support for situational factors overpowering the individual factors in determining the whistleblowing intentions. We found that ethical leadership was positively, and leader–member exchange negatively related with whistleblowing. In the presence of these situational factors, neither the Big Five personality traits, nor the moral foundations of a person seemed to matter in predicting an individual's whistleblowing behaviour.